Application of chitosan carbon / zinc oxide composite material in illumination decoloration regeneration of transformer waste oil and transformer waste oil refining method

By using the use of chitosan carbon/zinc oxide composite materials in the ultraviolet light to reduce the degradation transformer waste oil, it solves the problem that the existing technology is difficult to remove color impurities, and achieve efficient waste oil discoloration and regeneration.

CN119372012APending Publication Date: 2025-01-28STATE GRID HUBEI ELECTRIC POWER CO XIAOGAN POWER SUPPLY CO +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411551995.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove the color-induced impurities in the transformer waste oil, causing the waste oil to darken its color and affect its regeneration value.

Method used

The shell polycar carbon/zinc oxide composite material is mixed with the waste oil of the transformer, and the discoloration treatment is performed under ultraviolet light and mixing conditions.

Benefits of technology

This method can achieve more than 80%of the discoloration effect, effectively improve the color and electrical performance of waste oil, simplify the operation process and reduce the cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372012A_ABST
    Figure CN119372012A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of transformer waste oil refining and regeneration, and discloses application of a chitosan carbon / zinc oxide composite material in transformer waste oil illumination decoloration regeneration and a transformer waste oil refining method. The application comprises the following steps: mixing the chitosan carbon / zinc oxide composite material with transformer waste oil, decolorizing the waste oil under illumination and stirring conditions, and filtering to obtain transformer regenerated oil. The chitosan carbon / zinc oxide composite material is applied to decoloration and regeneration of transformer waste oil for the first time, and the decoloration effect can reach 80% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of transformer waste oil refining and regeneration, and more specifically, relates to application of chitosan carbon / zinc oxide composite material in light decolorization and regeneration of transformer waste oil and a transformer waste oil refining method. Background Art

[0002] Transformers are important power equipment, in which transformer oil plays a cooling and insulating role. Its stability and safety are one of the key links to ensure the reliable operation of electricity. The life of the transformer mainly depends on the insulating medium used. Under normal circumstances, transformer oil will gradually age and deteriorate under the influence of high temperature and electric field environment during the use of electrical equipment, and the electrical performance of the aged transformer oil will deteriorate significantly, resulting in a decrease in transformer efficiency. According to literature reports, the proportion of impurity products in transformer waste oil is very low, mainly including organic acids, particulate carbon, metal ions, trace moisture and colloids, etc., which appear yellow or dark brown due to the presence of some color-causing impurities. Despite this, most of the base oil components in transformer waste oil have not deteriorated, so transformer waste oil can be converted into recycled oil after reasonable refining treatment.

[0003] At present, the refining methods of transformer waste oil mainly include adsorption method and solvent extraction method. Among them, the solvent extraction method is to select a suitable solvent to selectively extract the basic components in the waste oil to obtain the recovered base oil, which plays a role in reducing emissions. However, the solvent extraction method has high requirements for the solvent, which requires a large solubility for the basic components in the transformer oil and a small solubility for the impurities in the waste oil. Therefore, this method is more suitable for the pretreatment process of transformer waste oil. Secondly, the adsorption method is a common method for decolorization and refining of transformer waste oil. It mainly uses a certain solid adsorption material, such as activated clay, activated carbon, etc., to remove harmful components in the waste oil through physical adsorption or chemical adsorption. The adsorbent adsorption method can effectively improve the color of the waste oil and enhance the electrical properties of the waste oil. Although the adsorption method has better effect and lower cost, the adsorbed material needs to be desorbed, so the operation process is longer and the desorption process is more complicated.

[0004] Light decolorization is an emerging oil refining technology. It is currently only used to remove natural pigments (such as anthocyanins, chlorophyll, etc.) in vegetable oils. Its application in transformer mineral oils has not yet been reported. According to literature reports, since natural pigments in vegetable oils can absorb the energy of visible light and near-ultraviolet light, the double bonds are oxidized, the structure of the chromophore group is destroyed, and the oil is decolorized. Different from the light decolorization mechanism of vegetable oils, the color-causing impurities in transformer mineral oils come from the oxidation products of mineral base oils or additives. The catalytic effect of photoactive materials is required to photodegrade the color-causing impurities by generating superoxide radicals and hydroxyl radicals. Therefore, photoactive materials are the core of light decolorization of transformer waste oil.

[0005] In order to achieve the goal of refining transformer waste oil, it is urgent to provide an application of polysaccharide carbon / zinc oxide composite material in light decolorization and regeneration of transformer waste oil and a method for refining transformer waste oil. Summary of the invention

[0006] The purpose of the present invention is to provide an application of a chitosan carbon / zinc oxide composite material in the light decolorization and regeneration of transformer waste oil and a method for refining transformer waste oil in view of the shortcomings of the prior art. The chitosan carbon / zinc oxide composite material of the present invention is firstly applied to the decolorization and regeneration of transformer waste oil, and the decolorization effect can reach more than 80%.

[0007] In order to achieve the above-mentioned purpose, the present invention provides, on the one hand, an application of a chitosan carbon / zinc oxide composite material in light decolorization and regeneration of transformer waste oil, wherein the application comprises mixing the chitosan carbon / zinc oxide composite material with transformer waste oil, decolorizing the waste oil under ultraviolet light and stirring conditions, filtering, and obtaining transformer regenerated oil.

[0008] According to the present invention, preferably, the mass ratio of the chitosan carbon / zinc oxide composite material to the transformer waste oil is 1:(2-10).

[0009] According to the present invention, preferably, the illumination time is 8-24h.

[0010] According to the present invention, preferably, the chitosan carbon / zinc oxide composite material is synthesized by a one-step hydrothermal method.

[0011] According to the present invention, preferably, the temperature of the hydrothermal reaction of the one-step hydrothermal method is 130-190° C., and the insulation time of the hydrothermal reaction is 12-24 h.

[0012] According to the present invention, preferably, the synthesis method of the chitosan carbon / zinc oxide composite material comprises the following steps:

[0013] S1: mixing zinc acetate, sodium hydroxide and deionized water to obtain a mixed solution;

[0014] S2: mixing the mixed system and chitosan to obtain a mixed system;

[0015] S3: sending the mixed system into a hydrothermal kettle lined with polytetrafluoroethylene for hydrothermal reaction to obtain a product, and washing and drying the product to obtain the chitosan carbon / zinc oxide composite material.

[0016] In the present invention, the purity specifications of the zinc acetate and sodium hydroxide are both 98%. The specification of the chitosan is a raw material with a deacetylation degree greater than or equal to 95%.

[0017] According to the present invention, preferably, the usage ratio of zinc acetate, sodium hydroxide and deionized water is (1.5-4): (0.8-1.2): 60 g / g / mL.

[0018] According to the present invention, preferably, the mass ratio of zinc acetate to chitosan is (0.5-6):1.

[0019] According to the present invention, preferably, in the step S1, the stirring rate is 200-600 r / min, and the stirring time is 5-20 min.

[0020] According to the present invention, preferably, in step S2: the stirring rate is 200-600 r / min, and the stirring time is 10-30 min.

[0021] According to the present invention, preferably, the washing liquid used in the washing is water and / or ethanol.

[0022] According to the present invention, preferably, the drying time is 12-24 hours.

[0023] Another aspect of the present invention provides a method for refining transformer waste oil, which comprises: mixing a chitosan carbon / zinc oxide composite material with transformer waste oil, decolorizing the waste oil under ultraviolet light and stirring conditions, filtering, and obtaining transformer regenerated oil.

[0024] According to the present invention, preferably, the mass ratio of the chitosan carbon / zinc oxide composite material to the transformer waste oil is 1:(2-10).

[0025] According to the present invention, preferably, the illumination time is 8-24h.

[0026] According to the present invention, preferably, the chitosan carbon / zinc oxide composite material is synthesized by a one-step hydrothermal method.

[0027] According to the present invention, preferably, the temperature of the hydrothermal reaction of the one-step hydrothermal method is 130-190° C., and the insulation time of the hydrothermal reaction is 12-24 h.

[0028] According to the present invention, preferably, the synthesis method of the chitosan carbon / zinc oxide composite material comprises the following steps:

[0029] S1: mixing zinc acetate, sodium hydroxide and deionized water to obtain a mixed solution;

[0030] S2: mixing the mixed system and chitosan to obtain a mixed system;

[0031] S3: sending the mixed system into a hydrothermal kettle lined with polytetrafluoroethylene for hydrothermal reaction to obtain a product, and washing and drying the product to obtain the chitosan carbon / zinc oxide composite material.

[0032] According to the present invention, preferably, the usage ratio of zinc acetate, sodium hydroxide and deionized water is (1.5-4): (0.8-1.2): 60 g / g / mL.

[0033] According to the present invention, preferably, the mass ratio of zinc acetate to chitosan is (0.5-6):1.

[0034] According to the present invention, preferably, in the step S1, the stirring rate is 200-600 r / min, and the stirring time is 5-20 min.

[0035] According to the present invention, preferably, in step S2: the stirring rate is 200-600 r / min, and the stirring time is 10-30 min.

[0036] According to the present invention, preferably, the washing liquid used in the washing is water and / or ethanol.

[0037] According to the present invention, preferably, the drying time is 12-24 hours.

[0038] The preparation method of the chitosan carbon / zinc oxide composite material of the present invention adopts a one-step hydrothermal reaction, has the advantages of simple operation, low cost, good reproducibility, mild reaction conditions, etc., and is suitable for popularization and application. In the prior art, a high-temperature calcination method is usually used to convert chitosan into carbon nanoparticles, while the present invention adopts a hydrothermal method, and in the process of preparing zinc oxide, chitosan is simultaneously converted into carbon nanoparticles, thereby avoiding the operation steps of secondary reactions and improving the preparation efficiency of the material.

[0039] The beneficial effects of the technical solution of the present invention are as follows:

[0040] The chitosan carbon / zinc oxide composite material of the present invention has a microstructure of zinc oxide nano-sheets loaded with carbon nano-particles, has a uniform morphology and good crystallinity. Due to the characteristics of zinc oxide nano-sheets stacked into nano-flowers, more active sites are exposed, which facilitates the photodegradation of coloring substances in transformer waste oil; chitosan is converted into nitrogen-doped carbon particles in a hydrothermal reaction, which are uniformly loaded on the surface of zinc oxide nano-sheets to form a heterogeneous structure of chitosan carbon and zinc oxide, which is beneficial to reducing the band gap of zinc oxide and contributing to the photodegradation and decolorization effect.

[0041] The chitosan carbon / zinc oxide composite material of the present invention is firstly applied to the decolorization and regeneration of transformer waste oil, and the decolorization effect can reach more than 80%. Transformer waste oil contains additive components such as mineral base oil and antioxidants. During long-term operation, the oil deteriorates and the color turns yellow or dark brown. Since the coloring substance is unknown, the current transformer waste oil decolorization mainly adopts the adsorption method. The light degradation method proposed in the present invention provides important support for technological innovation in this field.

[0042] The invention discloses a method for decolorizing transformer waste oil by using a chitosan carbon / zinc oxide composite material under ultraviolet light conditions, thereby avoiding the problems of a traditional adsorption method, such as a long operation process and difficulty in regenerating an adsorbent.

[0043] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention with reference to the accompanying drawings.

[0045] Figure 1 A comparison chart of the chitosan carbon / zinc oxide composite material in Example 1 of the present invention before and after light degradation of transformer waste oil is shown (left, dark color, transformer waste oil before light degradation; right, light color, transformer waste oil after light degradation).

[0046] Figure 2 The field emission scanning electron microscope image of the chitosan carbon / zinc oxide composite material of Example 1 of the present invention is shown.

[0047] Figure 3 The X-ray diffraction pattern (“Intensity” intensity, “2-Theta (degree)” angle) of the chitosan carbon / zinc oxide composite material of Example 1 of the present invention is shown.

[0048] Figure 4 The Fourier infrared image ("Transmittance", "Wavenumber") of the chitosan carbon / zinc oxide composite material of Example 1 of the present invention is shown.

[0049] Figure 5 The Raman spectrum ("Intensity", "Raman shift") of the chitosan carbon / zinc oxide composite material of Example 1 of the present invention is shown. DETAILED DESCRIPTION

[0050] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0051] Example 1

[0052] This embodiment provides a method for refining transformer waste oil, the refining method comprising:

[0053] (1) Preparation of the chitosan carbon / zinc oxide composite material

[0054] Add 60 mL of pure water, 0.5 g of zinc acetate and 0.25 g of sodium hydroxide into a beaker, add 0.1 g of chitosan after stirring for 15 min, stir until the solution is evenly mixed, transfer the mixed solution to a hydrothermal reactor with a polytetrafluoroethylene liner, react at a hydrothermal temperature of 160 ° C for 12 h, wait for the hydrothermal reactor to cool to room temperature, wash with pure water and anhydrous ethanol for 3 times respectively, put it in an oven and dry it at a temperature of 60 ° C for 12 h, grind the composite material after drying into powder to obtain a chitosan carbon / zinc oxide composite material with a yield of 82%.

[0055] (2) Light bleaching

[0056] Weigh 0.5g chitosan carbon / zinc oxide composite material into a 10mL specially made transparent quartz tube, then add 2g transformer waste oil, and irradiate for 12h under stirring and UV light conditions. Centrifugal separation to obtain transformer regenerated oil, such as Figure 1 As shown, the decolorization rate and acid value of the oil were tested. The decolorization rate of the transformer regeneration oil in this embodiment was 80.8%, and the acid value was 0.0135 mgKOH / g.

[0057] The chitosan carbon / zinc oxide composite material of Example 1 was analyzed using a field emission scanning electron microscope. Figure 2 As shown, zinc oxide nanosheets are evenly stacked together to form several nanosheet flower structures. Chitosan is converted into nanocarbon particles under high temperature and high pressure environment and loaded on the surface of the nanosheets to form a complex. The complex does not agglomerate, which is conducive to the attachment of color-causing organic matter.

[0058] The present invention uses X-ray diffraction to test the chitosan carbon / zinc oxide composite material of Example 1. Figure 3 As shown, the diffraction peaks of the chitosan carbon / zinc oxide composite material are complete and sharp, indicating that the composite material has a high degree of crystallinity. Compared with the zinc oxide standard card JCPDS (No. 36-1451), it can be determined that the diffraction peaks at diffraction angles of 31.71°, 34.39°, 36.22°, 47.64°, 56.58°, 62.78°, and 67.93° correspond to the (100), (002), (101), (102), (110), (103), and (112) crystal planes of zinc oxide, and the zinc oxide nanosheet has a hexagonal wurtzite structure.

[0059] The present invention uses Fourier transform infrared spectroscopy to analyze the chitosan carbon / zinc oxide composite material of Example 1. Figure 4 As shown, at 3442cm-1 The infrared peak at 2925cm is the vibration absorption peak of OH. -1 The stretching vibration peak at 1579 cm is the CH absorption peak of methyl or methylene. -1 The peak at is the stretching vibration absorption peak of C=O. This proves the successful composite of chitosan and carbon, and these functional groups will have a positive impact on the performance of the composite material.

[0060] The present invention further analyzes the carbonaceous structure of the chitosan carbon / zinc oxide composite material of Example 1 using Raman spectroscopy. Figure 5 As shown, at 1371 and 1577 cm -1 The characteristic peaks of D band and G band of chitosan carbon / zinc oxide composites were observed at . Among them, D band corresponds to disordered carbon in the composite material, and G band corresponds to graphite carbon in the composite material. According to the ratio of D band and G band peak height I D / I G is 0.89, indicating that the content of shaped carbon in the chitosan carbon / zinc oxide composite is higher than that of disordered carbon, which is beneficial to improving the specific surface area of ​​the composite and providing more active sites for the photodegradation process.

[0061] Example 2

[0062] This embodiment provides a method for refining transformer waste oil. The difference between this embodiment and embodiment 1 is only that:

[0063] (1) Synthesis of the chitosan carbon / zinc oxide composite material

[0064] The reaction was carried out at a hydrothermal temperature of 160°C for 6 hours to obtain a chitosan carbon / zinc oxide composite material.

[0065] (2) Light bleaching

[0066] The decolorization rate of the transformer regenerated oil in this embodiment is 75.2%, and the acid value is 0.0141 mgKOH / g.

[0067] Example 3

[0068] This embodiment provides a method for refining transformer waste oil. The difference between this embodiment and embodiment 1 is only that:

[0069] Step (1) is the same as that of Example 1;

[0070] (2) Light bleaching

[0071] Weigh 0.5g chitosan carbon / zinc oxide composite material in a 10mL special light-transmitting quartz tube, then add 4g transformer waste oil, and illuminate for 12h under stirring and ultraviolet light conditions. Centrifugal separation obtains transformer regenerated oil, and the decolorization rate and acid value of the oil are tested. The decolorization rate of the transformer regenerated oil in this embodiment is 62.1%, and the acid value is 0.0168mgKOH / g.

[0072] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. Application of chitosan carbon / zinc oxide composite material in light decolorization and regeneration of transformer waste oil, characterized in that: The application comprises mixing the chitosan carbon / zinc oxide composite material with transformer waste oil, decolorizing the waste oil under ultraviolet light and stirring conditions, filtering, and obtaining transformer regenerated oil.

2. The use according to claim 1, wherein: The mass ratio of the chitosan carbon / zinc oxide composite material to transformer waste oil is 1:(2-10).

3. The use according to claim 1, wherein: The illumination time is 8-24h.

4. The use according to claim 1, wherein: The chitosan carbon / zinc oxide composite material is synthesized by a one-step hydrothermal method; Preferably, the temperature of the hydrothermal reaction of the one-step hydrothermal method is 130-190° C., and the insulation time of the hydrothermal reaction is 12-24 h.

5. The use according to claim 4, wherein: The synthesis method of the chitosan carbon / zinc oxide composite material comprises the following steps: S1: mixing zinc acetate, sodium hydroxide and deionized water to obtain a mixed solution; S2: mixing the mixed system and chitosan to obtain a mixed system; S3: sending the mixed system into a hydrothermal kettle lined with polytetrafluoroethylene for hydrothermal reaction to obtain a product, and washing and drying the product to obtain the chitosan carbon / zinc oxide composite material; Preferably, the dosage ratio of zinc acetate, sodium hydroxide and deionized water is (1.5-4): (0.8-1.2): 60 g / g / mL; Preferably, the mass ratio of zinc acetate to chitosan is (0.5-6):1; Preferably, in step S1: the stirring rate is 200-600 r / min, and the stirring time is 5-20 min; Preferably, in step S2: the stirring rate is 200-600 r / min, and the stirring time is 10-30 min; Preferably, the washing liquid used in the washing is water and / or ethanol; Preferably, the drying time is 12-24 hours.

6. A method for refining waste transformer oil, characterized in that: The refining method comprises: mixing the chitosan carbon / zinc oxide composite material with transformer waste oil, decolorizing the waste oil under ultraviolet light and stirring conditions, filtering, and obtaining transformer regenerated oil.

7. The method for refining waste transformer oil according to claim 6, wherein: The mass ratio of the chitosan carbon / zinc oxide composite material to transformer waste oil is 1:(2-10).

8. The method for refining waste transformer oil according to claim 6, wherein: The illumination time is 8-24h.

9. The method for refining waste transformer oil according to claim 6, wherein: The chitosan carbon / zinc oxide composite material is synthesized by a one-step hydrothermal method; Preferably, the temperature of the hydrothermal reaction of the one-step hydrothermal method is 130-190° C., and the insulation time of the hydrothermal reaction is 12-24 h.

10. The method for refining waste transformer oil according to claim 9, wherein: The synthesis method of the chitosan carbon / zinc oxide composite material comprises the following steps: S1: mixing zinc acetate, sodium hydroxide and deionized water to obtain a mixed solution; S2: mixing the mixed system and chitosan to obtain a mixed system; S3: sending the mixed system into a hydrothermal kettle lined with polytetrafluoroethylene for hydrothermal reaction to obtain a product, and washing and drying the product to obtain the chitosan carbon / zinc oxide composite material; Preferably, the dosage ratio of zinc acetate, sodium hydroxide and deionized water is (1.5-4): (0.8-1.2): 60 g / g / mL; Preferably, the mass ratio of zinc acetate to chitosan is (0.5-6):1; Preferably, in step S1: the stirring rate is 200-600 r / min, and the stirring time is 5-20 min; Preferably, in step S2: the stirring rate is 200-600 r / min, and the stirring time is 10-30 min; Preferably, the washing liquid used in the washing is water and / or ethanol; Preferably, the drying time is 12-24 hours.